Improved Method for Differentiation of Synthetic and Natural Endogenous Anabolic Steroids using Gas Chromatography Isotope Ratio Mass Spectrometry (GC/C/IRMS) followed by Two-Fold High Performance Liquid Chromatography (HPLC) Cleanup Method: A Perspective - Shrivastava, Abhinav; Jain, Shila; Sahu, Puran Lal; Shukla, Sangeeta; Sahu, Kapendra (Indian Journal of Pharmaceutical Education and Research, 2019)
Background: Androgenic Anabolic Steroids (AAS) are also synthetic derivatives of testosterone, modified to improve its anabolic actions. The misuse of AAS is of particular concern in sports and society. Gas chromatography-mass spectrometry had some limitations and allows identification and characterization of steroids and their metabolites in the urine but may not be able to distinguish between pharmaceutical (Exogenous) and endogenous origin. Thus, it is of great importance to discriminate endogenous steroids such as testosterone or testosterone prohormones from their chemically identical synthetic copies. The abuse of Androgenic Anabolic Steroids (AAS) by sports person is banned by World Anti-doping Agency (WADA) as per the WADA Prohibited list 2019. Methodology: The gas chromatography-combustion/isotope ratio mass spectrometry (GC/C/IRMS) technique differentiates between natural and synthetic endogenous steroids by comparing compounds specific 13C/12C ratio. However, the analytes have to be efficiently isolated and purified prior to GC/C/IRMS analysis. Results and Discussion: HPLC Cleanup method prior to analysis by GC−C/IRMS needs to be developed and validated for discriminating the origin of anabolic androgenic steroids. These methods involves the solid-phase extraction, enzymatic hydrolysis with β-glucuronidase, HPLCfractionation for the cleanup and analysis by GC−C/IRMS. The difference (Δ13C) of urinary δ13C values between synthetic analogues and Endogenous Reference Compounds (ERC) by GC-C/IRMS would be used to elucidate the origin of steroids. The present perspective gives an overview of the use of anabolic-androgenic steroids in sport and methods used in anti-doping laboratories for their detection in urine, with special emphasis on GC−C/ IRMS technique after two-fold HPLC cleanup.
Keywords: Endogenous Steroids; Exogenous Steroids; HPLC Cleanup; Doping; GC/C/; IRMS